Modelling of vendor managed inventory with consignment stock in Indian production process: using ISM methodology. (10th December 2019) - Kumar, Mukesh; Garg, Dixit; Agarwal, Ashish
VMI with CS is a modern SCM adopted by Indian production process to survive in high competitive environment. The business performance is more profitable, economic and strategic by adaptation of VMI with CS model in an imperfect production environment and more competitive edges in multi dimensions aspects. With the help of literature survey group of cluster variables, four groups of cluster variables were identified. These are objectives variables, operational driver's variables, obstacle variables, and operation affected variables clusters in an imperfect production environment. The coordination mechanism has played a crucial role in an imperfect production and controlled all stages. Using ISM techniques for driving and dependent variables can easily be differentiated. The objective of the proposed framework is to develop business practices such as poor vendor's production process challenges and their control of production stages. The managerial implication to understand uncertain production environment, where delivery lead time and market demand fluctuates over long interval of time, provides research which may lead to win-win situation for each stake holder of SC.